2009
DOI: 10.1093/molbev/msp320
|View full text |Cite
|
Sign up to set email alerts
|

Divergence of the Mitochondrial Genome Structure in the Apicomplexan Parasites, Babesia and Theileria

Abstract: Mitochondrial (mt) genomes from diverse phylogenetic groups vary considerably in size, structure, and organization. The genus Plasmodium, causative agent of malaria, of the phylum Apicomplexa, has the smallest mt genome in the form of a circular and/or tandemly repeated linear element of 6 kb, encoding only three protein genes (cox1, cox3, and cob). The closely related genera Babesia and Theileria also have small mt genomes (6.6 kb) that are monomeric linear with an organization distinct from Plasmodium. To el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
100
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 45 publications
13
100
0
Order By: Relevance
“…Unlike their plastid counterparts, dinoflagellate mtDNAs can contain noncanonical start and stop codons (or none at all), transspliced genes, and oligonucleotide caps at both the 5′ and 3′ ends of transcripts (36,68). Many of these tendencies are consistent across other major alveolate groups as well (47,56,63,73).…”
Section: Convergent Organelle Genome Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike their plastid counterparts, dinoflagellate mtDNAs can contain noncanonical start and stop codons (or none at all), transspliced genes, and oligonucleotide caps at both the 5′ and 3′ ends of transcripts (36,68). Many of these tendencies are consistent across other major alveolate groups as well (47,56,63,73).…”
Section: Convergent Organelle Genome Evolutionmentioning
confidence: 99%
“…At one extreme are the giant mtDNAs of seed plants, like cucumber (∼1.6 Mb) (49) and Silene conica (∼11 Mb) (40), as well as those of diplonemids, which can exceed 500 kb (51). At the other end of the spectrum are the 6-kb mtDNAs of certain apicomplexans (56) and the fragmented mtDNA of their close relative C. velia, which is even smaller (57). Diminutive mtDNAs (<13 kb) have also been uncovered in green algae (44), ctenophores (58), and fungi (59).…”
Section: A Multiplicity Of Mitochondrial and Plastid Genome Architectmentioning
confidence: 99%
See 1 more Smart Citation
“…The lengths of mtDNa from B. gibsoni in our laboratory were 5,867 base pairs. The mtDNa of the B. gibsoni consisted of three functional genes, COXI, COXIII, and CYTb, and six discontinuous ribosomal RNA, as Hikosaka et al previously reported (NrcPD strain) [7]. additionally, terminal inverted …”
Section: Comparison Of Coxi Coxiii and Cytb Genes From Wildtype Andmentioning
confidence: 73%
“…These results indicated that Da did not directly affect mtDNa of the Da-resistant B. gibsoni. in general, COXI is one of 13 subunits of cytochrome c oxidase (complex iV), which is essential for electron transfer as a terminal oxidase in the respiratory chain [7,28]. COXIII is highly conserved in most of the heme-copper respiratory oxidase superfamily and is considered to be involved in the assembly and stabilization of the entire complex [7,28].…”
Section: Analysis Of Gene Transcription Of Coxi Coxiii and Cytb In mentioning
confidence: 99%